Implementation of Indigenous Knowledge Teaching Materials in Biology Learning Quasi-Experimental Study on Environmental Change Material - Hapsari, Melati Arum; Hariyatmi, H (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this study was to determine the biology learning outcomes of SMA Negeri 1 Teras class X students using teaching materials containing indigenous knowledge in the 2023/2024 school year on environmental change material. This type of quantitative research with a Quasi Experiment design, this form of Quasi Experiment uses Nonequivalent Control Group Design. This research was conducted in two classes, namely the control class and the experimental class. In this study, an initial test (pretest) was conducted before treatment and a final test (posttest) was conducted after treatment. A total of 72 students were sampled in this study. The research instrument was a test of cognitive, affective, and psychomotor learning outcomes. Analysis of learning outcomes data using normality test, homogeneity test and independent sample t-test test. The results of the calculation using the independent sample t-test test obtained a significance value (2-tailed) of 0.033 <0.050, so the null hypothesis (H0) is rejected. It can be concluded that the use of teaching materials containing Indigenous Knowledge is better and proven to have an effect on the learning outcomes of Biology class X students of SMA Negeri 1 Teras in the 2023/2024 school year on environmental change material.